The Freak Show's 'Missing Links': Krao Farini and the Pleasures of Archiving Prehistory. (1st October 2016) - Garascia, Ann
Abstract: This article offers a new perspective on Victorian freakery and prehistory by reading the career of Krao Farini, the 'Missing Link', through lenses of queer theory and archival studies. Born in Laos with hypertrichosis, a condition that produces an abundance of body hair, Krao transformed into living proof of the 'Missing Link' upon migrating to London in the 1880s. I contextualize Krao's exhibition by situating her show within contemporaneous visual, textual, and performed examples of the 'Missing Link'. Reading Krao alongside these other 'Missing Links' illuminates inconsistencies in their representations of gender and sexuality that nullify firm distinctions between 'pre' and 'history'. I argue that the freak show's 'Missing Link' materializes rhetorical and epistemological connections between Victorian prehistory and contemporary queer historiography to provide a valuable framework for accessing queer archives otherwise buried in the historical record. Though the correlations between prehistory and queer history are not necessarily explicit, locating their similarities reveals how persistent notions of Victorian time inform contemporary queer scholarship. Presaging recent queer archival interventions, Krao's remaining archive demonstrates how prehistory breeds alternative models of evidence that disorder the archive's relation to time: evidence of the 'Missing Link' unravels the language of stability, family, and presence on which archives typically rest. Resisting the implicitly heteronormative logic of the archival document, prehistory makes possible new ways of narrating Victorian histories of freakery, imperialism, and gender and sexuality.